COMPARISON OF SUCCESS RATE OF FRONTAL VERSUS OCCIPITAL ENTRY SITE FOR VENTRICULOPERITONEAL SHUNT INSERTION IN PATIENTS WITH HYDROCEPHALUS (Journal of Medical & Health Sciences Review, 2025)
Background: Hydrocephalus is a common neurological disorder characterized by an abnormal accumulation of cerebrospinal fluid within the brain ventricles. Surgical interventions, such as ventriculoperitoneal (VP) shunt insertion, are often necessary to manage this condition. However, the choice of entry site for VP shunt insertion, whether frontal (Kocher's entry site) or occipital (Frazier’s entry point), remains a matter of debate.Objectives: The objective of this study is to compare the success rate of frontal (Kocher's entry site) versus occipital (Frazier’s entry point) entry sites for ventricular catheter tip placement in patients with hydrocephalus.Study Design: This study utilizes a quasi-experimental design, focusing on non-randomized trial methods. Data collection is conducted prospectively over a one-year period, from June 2022 to June 2023 at Punjab institute of neurosciences, Unit 3, Lahore.Patients and Methods: The study includes 60 patients of both genders (30 in each group), aged between 10 and 60 years with obstructive and communicating hydrocephalus. Postoperative assessments include evaluations of consciousness level, clinical outcomes, and the incidence of infections. Follow-up assessments up to six months post-surgery are conducted to monitor shunt-related complications such as obstruction, over drainage, and malposition.Results: Overall success rate of VP shunt through frontal (Kocher's point) was 80% as compared to 66% in occipital (Frazier’s entry point). Total 20% cases showed malposition of which 6.67% were from VP shunt through Kocher point and 13.3% from Frazier point shunt. Rate of infection was 10% in VP shunt through Kocher and 3.3 % in VP shunt through Frazier point. 6.67% cases showed overdrainge and all these cases belong to VP shunt through Frazier point. Obstruction was observed in 3.33% cases in Kocher and 10% in VP shunt through Frazier.Conclusion: The study revealed a notable disparity in the overall success rates between VP shunt placements through frontal (Kocher's point) and occipital (Frazier’s entry point) approaches.  Frontal approach demonstrated a higher success rate compared to the occipital approach, the choice of entry site should be carefully considered based on individual patient factors and surgical preferences. Further research focusing on the underlying mechanisms contributing to these differences is crucial for refining surgical techniques and improving patient care in hydrocephalus management.